The Role of Biomethane from Sewage Sludge in the Energy Transition: Potentials and Barriers in the Arab Gulf States Power Sector - Mohammad Alshawaf (MDPI AG, 2021)
The increasing energy and water demands by the Arab Gulf states highlight the importance of sustainable use of energy resources. Wastewater sludge management for energy recovery creates an opportunity for sector integration for both wastewater treatment plants and renewable energy production. The objective of this study was to theoretically estimate the biomethane potential of wastewater sludge, together with identification of the role of biomethane in the region. The prediction of biomethane potential was based on the theoretical stoichiometry of biomethanation reactions, using the R-based package ‘Process Biogas Data and Predict Biogas Production’. The biomethane potential of sludge ranges between 232–334 × 106 m3, with a total heat-value up to 10.7 trillion BTUs annually. The produced biomethane can generate up to 1665 GWh of electric energy, an equivalent amount to the current levels of electricity generation from wind and solar power combined. The findings from the case study on Kuwait’s indicate that biomethane could displace 13 × 106 m3 of natural gas, or approximately 86,000 barrels of crude oil, while simultaneously reducing greenhouse gas emissions by 86% when compared to the base-scenario. Despite its potential, biomethane recovery in the region is hindered by technical-, economic-, and policy-based barriers.